Analyzing Student Representative of ITB Consultative Assembly Engagement Related to Leadership Style - Hasudungan, Lumban Gaol Beres; Rahmatsyah Putranto, Nur Arief (Journal of Business and Management, 2019)
Leadership is one of the key determinants associated with the success or failure of any organization. Many organizations believe that many factors influence level of engagement in an organization, but this study has focused on specific factor, namely leadership style. Researcher interested to analyze the student representative of ITB Consultative assembly engagement related to leadership style. The purpose of this study was to find the relationship and significant relationship between transformational and transactional leadership style to member engagement. Data was obtained through the combined distribution of two the questionnaires. The multifactor leadership questionnaire, used to measure transformational and transactional leadership, and the Gallup Q12, used to measure the member engagement. In this study, researcher used multiple regression analysis method for the statistical analysis. Total respondents for this research are 75 respondents. The result of this analysis shown that transformational and transactional has positive relationship and significant relationship to the member engagement. This study recommends that leaders can improving the transformational and transactional leadership style to increase their attitude in encouraged, gives support and appreciate, and motivated to the member. Thus, the member can be actively engaged in their work.